Moringa olifera leave extracts yielded from irradiated and unirradiated seeds cause toxicity and induce dysregulation of enzymatic activities in fall armyworm, Spodoptera frugiperda (JE Smith, 1797) [Lepidoptera: Noctuidae] - Salwa Abdou Rizk; Rehab Mahmoud Sayed; Tammy Samir El sayed (Discover Applied Sciences)
Abstract The fall armyworm, Spodoptera frugiperda is the most distractive polyphagous noctuid pest in tropical and subtropical regions. The current study was designed to examine the insecticidal activity of the water extract of Moringa olifiera leaves cultivated from unirradiated and 40 Gy irradiated seeds. Also, the effect of the extract on some digestive enzymes activities was assayed. The results indicated that the extract produced from 40 Gy irradiated seeds was more effective than those of unirradiated one. As well as, leaves extract produced from cultivated irradiated and unirradiated seeds decrease lipase protease and amylase activities of 3rd instar larvae of S. frugiperda and the highest decrease was in larvae fed on leaves produced from irradiated cultivated seeds. Therefore, the water extract of M. olifiera leaves cultivated from 40 Gy irradiated seeds might be seen as an environmentally beneficial pest management method.